Frost Resistance Number to Assess Freeze and Thaw Resistance of Non-Autoclaved Aerated Concretes Containing Ground Granulated Blast-Furnace Slag and Micro-Silica - Sharafutdinov, Eldar; Shon, Chang-Seon; Zhang, Dichuan; Chung, Chul-Woo; Kim, Jong; Bagitova, Saltanat (MDPI, 2019)
Aerated concrete (AC), such as cellular concrete, autoclaved aerated concrete (AAC), and non-autoclaved aerated concrete (NAAC), having excellent insulation properties, is commonly used in buildings located in cold regions, such as Nur-Sultan in Kazakhstan, the second coldest capital city in the world, because it can contribute to a large energy saving. However, when the AC is directly exposed to the repeated freeze and thaw (F-T) cycles, its F-T resistance can be critical because of lower density and scaling resistance of the AC. Moreover, the evaluation of the F-T resistance of the AC based on the durability factor (DF) calculated by using the relative dynamic modulus of elasticity may overestimate the frost resistance of the AC due to the millions of evenly distributed air voids in spite of its weak scaling resistance. In the present study, the F-T resistance of NAAC mixtures with various binary or ternary combinations of ground granulated blast-furnace slag (GGBFS) and micro-silica was assessed mainly using the ASTM C 1262/C1262M-16 Standard Test Method for Evaluating the Freeze-Thaw Durability of Dry-Cast Segmental Retaining Wall Units and Related Concrete Units. Critical parameters to affect the F-T resistance performance of the NAAC mixture such as compressive strength, density, water absorption, air–void ratio (VR), moisture uptake, durability factor (DF), weight loss (Wloss), the degree of saturation (Sd), and residual strength (Sres) were determined. Based on the determined parameter values, frost resistance number (FRN) has been developed to evaluate the F-T resistance of the NAAC mixture. Test results showed that all NAAC mixtures had good F-T resistance when they were evaluated with DF. Binary NAAC mixtures generally showed higher Sd and Wloss and lower DF and Sres than those of ternary NAAC mixtures. It was determined that the Sd was a key factor for the F-T resistance of NAAC mixtures. Finally, the developed FRN could be an appropriate tool to evaluate the F-T resistance of the NAAC mixture